2020
DOI: 10.1186/s13568-020-01106-3
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamic changes of the fecal bacterial community in dairy cows during early lactation

Abstract: The dynamics of the community structure and composition of the dairy cow fecal bacterial communities during early lactation is unclear, therefore this study was conducted to characterize the fecal bacterial communities in dairy cows during early lactation using 16S rRNA gene sequencing. Feces were sampled from 20 healthy fresh Holstein dairy cows on day 1 (Fresh1d group) and day 14 (Fresh14d group) after calving. After calving, cows were fed the same fresh diet. The dominant phyla Firmicutes and Proteobacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 50 publications
6
9
0
Order By: Relevance
“…This would explain why PLFA data indicate the dominance of Gram + bacteria in faeces, whereas DNA sequencing approaches usually find markedly more Gram-bacteria (Pitta et al 2016;Jose et al 2017;Kala et al 2017;Thomas et al 2017). However, Kim et al (2014) observed a dominant contribution of Gram + Firmicutes, ranging between 50 and 77% of total sequences caused by differences in diet, which is in line with recent results of others (Faulkner et al 2017;Cendron et al 2020;Huang et al 2020).…”
Section: Bacterial Abundancesupporting
confidence: 90%
“…This would explain why PLFA data indicate the dominance of Gram + bacteria in faeces, whereas DNA sequencing approaches usually find markedly more Gram-bacteria (Pitta et al 2016;Jose et al 2017;Kala et al 2017;Thomas et al 2017). However, Kim et al (2014) observed a dominant contribution of Gram + Firmicutes, ranging between 50 and 77% of total sequences caused by differences in diet, which is in line with recent results of others (Faulkner et al 2017;Cendron et al 2020;Huang et al 2020).…”
Section: Bacterial Abundancesupporting
confidence: 90%
“…Especially farm animals e.g. cattle [ 4 6 ], pigs [ 7 9 ] or sheep [ 10 , 11 ], have been largely analyzed due to their importance in agriculture. The microbiota of some wild species, especially highly endangered species such as black rhinos [ 12 ], koalas [ 13 ] and Tasmanian devils [ 14 ], has also been described in more detailed studies.…”
Section: Introductionmentioning
confidence: 99%
“…There have been few reports on the effect of lactation stages in ruminants on faecal microbiota composition. The report of Huang et al [28] shows a significant effect of lactation period on diversity at the phylum level in the faecal bacterial community. This means that lactation stages induce a variation in the faecal bacterial community [28].…”
Section: Discussionmentioning
confidence: 94%